Patterns and drivers of prokaryotic communities in thermokarst lake water across Northern Hemisphere - Luyao Kang; Leiyi Chen; Ziliang Li; Jianjun Wang; Kai Xue; Ye Deng; Manuel Delgado‐Baquerizo; Yutong Song; Dianye Zhang; Guibiao Yang; Wei Zhou; Xuning Liu; et al. (Global Ecology and Biogeography, 2023)
Aim The formation of thermokarst lakes could make a large amount of carbon accessible to microbial degradation, potentially intensifying the permafrost carbon‐climate feedback via carbon dioxide/methane emissions. Because of their diverse functional roles, prokaryotes could strongly mediate biogeochemical cycles in thermokarst lakes. However, little is known about the large‐scale patterns and drivers of these communities. Location Permafrost regions in the Northern Hemisphere. Time period Present day. Major taxa studied Prokaryotes. Methods Based on a combination of large‐scale measurements on the Tibetan Plateau and data syntheses in pan‐Arctic regions, we constructed a comprehensive dataset of 16S rRNA sequences from 258 thermokarst lakes across Northern Hemisphere permafrost regions. We also used the local contributions to beta diversity (LCBD) to characterize the variance of prokaryotic species composition and screened underlying drivers by conducting a random forest modelling analysis. Results Prokaryotes in thermokarst lake water were dominated by the orders Burkholderiales, Micrococcales, Flavobacteriales and Frankiales. The relative abundance of dominant taxa was positively associated with dissolved organic matter (DOM) properties, especially for the chromophoric/aromatic compounds. Microbial structure differed between high‐altitude and high‐latitude thermokarst lakes, with the dominance of Flavobacterium in high‐altitude lakes, and the enrichment of Polynucleobacter in high‐latitude lakes. More importantly, climatic variables were among the main drivers shaping the large‐scale variation of prokaryotic communities. Specifically, mean annual precipitation was the best predictor for prokaryotic beta diversity across the Northern Hemisphere, as well as in the high‐altitude permafrost regions, while mean annual air temperature played a key role in the high‐latitude thermokarst lakes. Main conclusions Our findings demonstrate significant associations between dominant taxa and DOM properties, as well as the important role of climatic factors in affecting prokaryotic communities. These findings suggest that climatic change may alter DOM conditions and induce dynamics in prokaryotic communities of thermokarst lake water in the Northern Hemisphere.